Biomarkers to predict FDG PET/CT activity after the standard duration of treatment for spinal tuberculosis: An exploratory study. (July 2021) - Mann, Theresa N.; Warwick, James; Chegou, Novel N.; Davis, Johan H.; Beltran, Caroline G.G.; Griffith-Richards, Stephanie; Kidd, Martin; du Toit, Jacques; Lamberts, Robert P.; Walzl, Gerhard
Abstract: Objectives: 18F-Fluorodeoxyglucose (FDG) Positron Emission Tomography- Computed Tomography (PET/CT) scans can be used to assess healing following treatment for spinal tuberculosis (TB) but have limited accessibility and high cost. This study investigated the association between immune biomarkers and FDG-PET/CT activity after ≥9 months of treatment for spinal TB. Methods: Patients who had completed ≥9 months of treatment for spinal TB were recruited from a major hospital in the Western Cape, South Africa. Participants underwent a FDG-PET/CT scan and FDG- PET/CT activity was quantified for all spinal and extra-spinal sites. Participants also provided a blood sample, which was evaluated for 19 cytokines along with erythrocyte sedimentation rate (ESR). Correlations and multiple regression analyses were used to investigate the association between biomarkers and PET/CT measures. Results: Twenty-eight patients were recruited, of whom 24 (86%) had spinal and/or extra-spinal FDG-PET/CT activity. In the strongest multiple regression model, CXCL10/IP-10, VEGFA, IFN-γ, CRP and Factor D/Adipsin explained 52% of the variation in overall maximal FDG uptake. Conventional monitoring marker ESR showed no significant association with PET/CT measures. Conclusions: The current findings offered encouragement that biomarkers to predict FDG-PET/CT activity may show some promise and identified candidate biomarkers for further investigation in this regard. Highlights: Most individuals still had FDG-PET/CT activity at the spine lesion after ≥9 months of TB treatment. Conventional monitoring marker ESR showed no association with FDG-PET/CT activity. A novel five-biomarker signature explained 52% of maximal FDG-PET/CT activity. Biomarker/PET/CT associations varied with HIV status and/or previous TB.